Poly ADP-Ribosylation in a Plant Pathogenic Oomycete Phytophthora infestans: A Key Controller of Growth and Host Plant Colonisation - Viktoriya O. Samarskaya; Sofya Koblova; Tatiana Suprunova; Eugene A. Rogozhin; Nadezhda Spechenkova; Sofiya Yakunina; Andrew J. Love; Natalia O. Kalinina; Michael Taliansky (Journal of Fungi)
ADP-ribosylation is a reversible modification of proteins and nucleic acids, which controls major cellular processes, including DNA damage repair, cell proliferation and differentiation, metabolism, stress, and immunity in plants and animals. The involvement of ADP-ribosylation in the life cycle of Dictyostelium and some filamentous fungi has also been demonstrated. However, the role of this process in pathogenic oomycetes has never been addressed. Here, we show that the Phytophthora infestans genome contains two PARP-like protein genes (PiPARP1 and PiPARP2), and provide evidence of PARylation activity for one of them (PiPARP2). Using dsRNA-mediated RNA silencing of the PiPARP2 gene and chemical (pharmacological) inhibition of PARP activity by 3-aminobenzamide (3AB) PARP inhibitor, we demonstrate the critical functional role of ADP-ribosylation in Phytophthora mycelium growth. Virulence test on detached leaves also suggests an important role of ADP-ribosylation in Phytophthora host plant colonisation and pathogenesis. On a practical level, our data suggest that targeting the PARylation system may constitute a novel powerful approach for the management of Phytophthora diseases.